Hardy-Weinberg Equilibrium as Foundational - Stark, Alan E.; Seneta, Eugene (International Journal of Statistics in Medical Research, 2014)
The Hardy-Weinberg Principle explains how random mating can produce and maintain a population in equilibrium, that is: with constant genotypic proportions. The Hardy-Weinberg formula is in constant use as a basis for developing population genetics theory. Here we give a complete description of a model which can sustain equilibrium but with a general mating system, thereby giving a much broader basis on which to develop population genetics. It was S. N. Bernstein who first showed how Mendel’s first law could be justified simply on the basis of observations of populations in equilibrium. We show how the model can be applied to exploring the change in incidence of a genetic disorder.